Acute on chronic liver failure because of acute hepatic insults: Etiologies, course, extrahepatic organ failure and predictors of mortality. Issue 4 (April 2016) - Shalimar,; Kumar, Dharmendra; Vadiraja, Padmaprakash Kadavoor; Nayak, Baibaswata; Thakur, Bhaskar; Das, Prasenjit; Datta Gupta, Siddhartha; Panda, Subrat Kumar; Acharya, Subrat Kumar
Abstract: Background and Aim: Acute on chronic liver failure (ACLF) because of precipitating factors (variceal bleed/infections) identifies cirrhotics at risk for high short‐term mortality. Information on ACLF because of acute hepatic insults is lacking. The aim of the study was to evaluate acute hepatic insults in ACLF and their effect on the course and outcome. Methods: In a prospective study, 213 consecutive patients of ACLF because of acute hepatic insults were included. Etiology of acute hepatic insult, frequency of silent, and overt chronic liver disease (CLD), organ failure (OF), and outcomes were assessed. Prognostic models such as model for endstage liver disease (MELD), acute physiology and chronic health evaluation (APACHE II), and chronic liver failure‐sequential organ failure (CLIF‐SOFA) were evaluated. Results: Etiologies of acute hepatic insult were hepatitis virus(es)‐ 81 (38%; HBV‐42, HEV‐39), continuous alcohol consumption‐77 (33.3%), antituberculosis drugs‐11 (5.2%), autoimmune hepatitis flare‐5(2.3%), cryptogenic‐44 (20.7%). The common causes of CLD were alcohol ( n = 85/40%), HBV( n = 52/24%), and cryptogenic( n = 50/20%). The MELD, APACHE II, and CLIF‐SOFA scores were similar among silent and overt CLD and did not influence outcome. Predominant etiologies of ACLF were hepatitis virus(es) reactivation or superinfection in silent CLD(52/112, 46.4%) and alcohol among overt CLD(43/101, 43%). Independent predictors of mortality included hepatic‐encephalopathy (early, HR: 4.01; advanced, HR: 6.10), serum creatinine ≥1.5 mg/dl (HR: 4.53), CLIF‐SOFA ≥8(HR: 1.69), and etiology of acute hepatic insult (alcohol, HR: 4.08; cryptogenic, HR: 3.18). HEV‐ACLF had lower mortality (12.8% vs. 33–54% in other etiologies; P < 0.001). OF was major determinant of mortality. With increasing number of OF, mortality increased linearly( P = 0.001). Conclusions: Hepatitis virus(es) and continuous alcohol consumption are important causes of ACLF caused by acute hepatic insults. HEV‐ACLF has lower mortality. OF is an important prognostic predictor.